Program Pencegahan Penyakit Tidak Menular pada Lansia melalui Pemeriksaan Kesehatan dan Penyuluhan Gizi Seimbang di Bondowoso - Ningtyias, Farida Wahyu; Septiani, Baiq Dewi Sukma; Fitriyah, Holif (Kolaborasi: Jurnal Pengabdian Masyarakat, 2025)
Introduction: Non-communicable diseases (NCDs), such as hypertension, diabetes, and stroke, are common among the elderly and impact their quality of life. In Bondowoso, the high prevalence of hypertension emphasizes the need for preventive and promotive efforts. Regular health checks and balanced nutrition counseling are key strategies for early detection and risk management. Objective: This Community Service Program aims to improve the well-being of the elderly in Bondowoso and provide a sustainable model for community-based NCD prevention. Methods: 34 elderly individuals aged 60 and above participated in health checks and balanced nutrition counseling, including group sessions on healthy eating patterns, balanced menu planning, and local foods beneficial for elderly health. The program was tailored to meet the specific needs of the participants. Results: Health checks revealed a high prevalence of NCDs: 65% had hypertension, 76.5% had diabetes, and 82.4% were at risk for metabolic syndrome. Despite most participants exhibiting healthy behaviors, such as consuming ≥400g of fruits and vegetables daily (79.4%) and engaging in regular physical activity (70.6%), the high risk of NCDs emphasized the importance of continued health management and education. Conclusion: The program effectively raised awareness of NCD risk factors and demonstrated the importance of early detection and balanced nutrition education in improving the quality of life for the elderly in Bondowoso.